AN ANALYSIS TRANSLATION OF FIGURE OF SPEECH IN THE NOVEL “TO ALL THE BOYS I’VE LOVED BEFORE” - Miftah Kevin Iswara; Evert Haryanto Hilman (Asosiasi dosen IDEBAHASA KEPRI, 2022)
This research is entitled an analysis of figurative language in novel